'Balancing risk' after fall‐induced hip fracture: the older person's need for information. (24th April 2013) - McMillan, Laura; Booth, Joanne; Currie, Kay; Howe, Tracey
<x xml:space="preserve">Abstract</x> Background Hip fracture is a significant cause of morbidity and mortality in older people. Healthcare professionals have a role to identify and respond to challenges and concerns that older people face as they strive to manage risk of future falls and rebuild confidence and independence after discharge. Aims and objectives This study aimed to explore the postdischarge concerns of older people after fall‐induced hip fracture. Method Glaser's approach to the grounded theory method guided qualitative interviews conducted with 19 older people in their own homes up to 3 months post discharge, in two health authority areas. Results A theory of 'taking control' was generated. 'Balancing risk' emerged as a key strategy that older people employed to help them to take control after discharge home. Older people attempted to control or 'balance' their risk of future falls and dependence by implementing two further strategies: 'protective guarding' and 'following orders'. The instinctive strategy of protective guarding and the learned strategy of following orders were implemented simultaneously and were characterised by older people aiming to pace their progress and balance risk safely and appropriately. To apply these strategies, older people required information from healthcare professionals. In circumstances where older people did not receive or did not understand the information provided, they were left 'grasping to understand' and were more likely to miscalculate risk. This leads to damaged confidence and in some cases further falls. Conclusions The concept of balancing risk aims to help healthcare professionals understand the older person's perspective of hip fracture and to recognise the efforts that people make to guard against further injury and dependence in the early postdischarge period. Implications for practice Our study suggests that engaging older people and their relatives in discussions to acknowledge their perceptions of future risk and to provide appropriate information on managing risk is crucial, as this will enable older people to balance risk safely and ultimately rebuild independence.